Synthesis and photoluminescence properties in white light-emitting diodes of oxynitride green phosphor Ba3Si6O12N2 - Dieu An Nguyen Thi; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
Utilizing boron-coated Eu2O3, highly effective Ba3Si6O12N2 green-emitting phosphors were made using a gas reduction nitridation technique under flowing NH3 gas. We found that the synthesized phosphor is a pure phase of Ba3Si6O12N2 based on X-ray diffraction patterns. By modifying an alumina boat crystallized, the Ba3Si6O12N2 green-emitting phosphors from the result were considerably better and had higher emission intensity. Under stimulation at 405 nm, the radiation spectra revealed a typical wide green radiation band attributable to the 4f65d → 4f7 electronic transfer of Eu2+ ions. Generally, the green-emitting Ba3Si6O12N2 phosphors that were created by that method with boron-coated Eu2O3 is a potential phosphor-transformed diodes which emit white illumination white light emitting diodes(pc-WLEDs') element.